Bridging the knowledge divide : educational technology for development - Marshall, Stewart; Kinuthia, Wanjira; Taylor, Wallace, 1944- (Emerald Publishing Limited : Information Age Publishing, 2009)
In many international settings, developing economies are in danger of declining as the digital divide becomes the knowledge divide. This decline attacks the very fabric of cohesion and purpose for these regional societies delivering increased social, health, economic and sustainability problems. The examples in this book will provide leaders, policy developers, researchers, students and community with successful strategies and principles of ICT use in education to address these needs.This book will discuss how educational technology can be used to transform education and assist developing communities to close the knowledge divide. It will provide comprehensive coverage of educational technology in development in different professions and parts of world. The book will provide examples of best practice, case studies and principles for educators, community leaders, researchers and policy advisers on the use of educational technology for development. In particular, it will provide examples of how education can be provided more flexibly in order to provide access to hitherto disadvantaged communities and individuals.
Keywords: Educational technology -- Economic aspects -- Developing countries.; Economic development -- Effect of technological innovations on -- Developing countries.; Education -- Computers & Technology.; Development economics and emerging economies.; Educational equipment and technology, computer-aided learning (CAL); elektronické knihy; electronic books